1999
DOI: 10.1074/jbc.274.50.35668
|View full text |Cite
|
Sign up to set email alerts
|

Dual Roles for Transcription Factor IIF in Promoter Escape by RNA Polymerase II

Abstract: Transcription factor (TF) IIF is a multifunctional RNA polymerase II transcription factor that has well established roles in both transcription initiation, where it functions as a component of the preinitiation complex and is required for formation of the open complex and synthesis of the first phosphodiester bond of nascent transcripts, and in transcription elongation, where it is capable of interacting directly with the ternary elongation complex and stimulating the rate of transcription. In this report, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 57 publications
(37 reference statements)
4
54
1
Order By: Relevance
“…Previous studies have shown (i) that TFIIH and an ATP(dATP) cofactor are dispensable for initiation by RNA polymerase II from the Ad(Ϫ9͞Ϫ1) promoter but are required for efficient promoter escape (3), and (ii) that TFIIH and an ATP(dATP) cofactor are not required for either transcription initiation or promoter escape by RNA polymerase II from the Ad(Ϫ9͞ϩ9) promoter (5). As illustrated in Fig.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…Previous studies have shown (i) that TFIIH and an ATP(dATP) cofactor are dispensable for initiation by RNA polymerase II from the Ad(Ϫ9͞Ϫ1) promoter but are required for efficient promoter escape (3), and (ii) that TFIIH and an ATP(dATP) cofactor are not required for either transcription initiation or promoter escape by RNA polymerase II from the Ad(Ϫ9͞ϩ9) promoter (5). As illustrated in Fig.…”
Section: Resultsmentioning
confidence: 85%
“…Results of previous experiments suggest that a TFIIF activity required for transcription initiation presents an impediment to efficient promoter escape and is at least partly responsible for inducing the premature arrest of very early RNA polymerase II elongation intermediates (5). Together with results of cross-linking experiments suggesting that TFIIF and TFIIE promote tight wrapping of DNA around RNA polymerase II by making contacts in the initiation complex with promoter DNA upstream of the TATA box and downstream of the transcriptional start site (10,11,41), this observation raises the possibility that protein-DNA contacts between promoter DNA and TFIIF and TFIIE might present an impediment to promoter escape.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, this domain binds DNA and is required for initiation 21 , and TFIIF suppresses abortive initial transcription 22 . The proximity of the Tfg2 WH domain to TFIIB indicates how TFIIF could stabilize TFIIB on Pol II during initial transcription 23 .…”
Section: Resultsmentioning
confidence: 99%